Sound Change and Analogy: the Synchronic Reflexes of the Second Compensatory Lengthening in Ancient Greek Dialects (Mudança Sonora e Analogia: Reflexo Sincrônico do Alongamento Secundário Compensatório em Dialeto do Grego Antigo) - Wetzels, Willem Leo (Estudos da Língua(gem), 2006)
No grego, em variadas situações, vogais curtas tornam-se longas para compensar a perda ou a ressilabificação de uma consoante adjacente. Neste artigo, discute-se o processo conhecido na literatura helenística como ‘alongamento compensatório secundário’. Essa regra afeta seqüências Vns intervocálicas e de final de palavra. Discute-se o reflexo sincrônico da seqüência Vns em dialetos do grego antigo e mostra-se que a variação dialetal pode ser explicada parcialmente como o efeito de reestruturação lexical, ou nivelamento analógico. PALAVRAS-CHAVE: Mudança Sonora. Analogia. Ditongo variável. Alongamento compensatório. Grego Antigo. ABSTRACT In early Greek, at several occasions short vowels became long to compensate for the loss or the resyllabification of a neighbouring consonant. Here we will discuss the process that is known in the Hellenistic literature as the ‘Second Compensatory Lengthening’. This rule affected intervocalic and word-final Vns sequences, in a manner that was different for the various dialects. We will discuss the synchronic reflexes of the Vns sequence in the Ancient Greek dialects and show that the dialectal variation can be explained partly as a result of differences in the nature of the consonant deletion rule, and partly as the effect of lexical restructuring-cum-rule-loss, or analogical levelling. KEYWORDS: Sound change. Analogy. Mobile diphthong. Compensatory lengthening. Ancient Greek.